2020
DOI: 10.1155/2020/4270957
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Expressions of CXCL9/10/12/13 as Prognosis Factors in Breast Cancer

Abstract: CXCLs play critical roles in antitumor immunity by activating tumor-specific immune responses and stimulating tumor proliferation, thus affecting patient outcomes. However, the expression and prognostic values of CXCLs in breast cancer have not been well clarified. The aim of this study was to investigate the impact of CXCLs transcriptional expression on breast cancer patients. Oncomine database, GEPIA (Gene Expression Profiling Interactive Analysis), UALCAN, Kaplan–Meier Plotter, TIMER (Tumor Immune Estimatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
41
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(49 citation statements)
references
References 35 publications
7
41
0
1
Order By: Relevance
“…Our findings are in line with previous studies which have shown that increased Ifn expression, Ifn signaling, and activity of the Cxcl9/10-Cxcr3 chemokine axis are associated with improved prognosis for a variety of solid tumors. [23][24][25][26][27] Ifn expression in the TME has been described to enhance tumor cell killing through differentiation and activation of CD8+ T cells, rescue of exhausted CD8+ T cells, and upregulation of MHC class II in various immune cell populations. 27,28 Meta-analysis studies of patient data consistently correlate Ifn gene signatures with better prognoses, 24,29 and loss of Ifn appears to correlate with resistance to checkpoint inhibition therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are in line with previous studies which have shown that increased Ifn expression, Ifn signaling, and activity of the Cxcl9/10-Cxcr3 chemokine axis are associated with improved prognosis for a variety of solid tumors. [23][24][25][26][27] Ifn expression in the TME has been described to enhance tumor cell killing through differentiation and activation of CD8+ T cells, rescue of exhausted CD8+ T cells, and upregulation of MHC class II in various immune cell populations. 27,28 Meta-analysis studies of patient data consistently correlate Ifn gene signatures with better prognoses, 24,29 and loss of Ifn appears to correlate with resistance to checkpoint inhibition therapy.…”
Section: Discussionmentioning
confidence: 99%
“…HMGB1 is one of the damage-associated molecular patterns (DAMP) and plays a multifunctional role in inflammation and the development of cancer (such as colorectal cancer) [32,33]. It has been reported that CXCL9 is associated with the infiltration of immune cells and affects the prognosis of breast cancer patients [34]. HAVCR2 inhibitors have been proven to have certain tumor-suppressive effects in various preclinical tumor models [35].…”
Section: Discussionmentioning
confidence: 99%
“…ER-Negative Breast Cancer patients also showed a good prognosis associated with immune cells infiltration in suggesting CXCL9 as a potential biomarker for the prognosis of this disease [ 224 ]. Another recent study also reported that in breast cancer high expression of CXCL9 and CXCL10 is associated with a good prognosis [ 225 ].…”
Section: Key Chemokine-chemokine Receptor Interactions That Limit Tumor Growthmentioning
confidence: 99%
“…CXCL10 is largely produced by monocytic cells, endothelial cells, and fibroblasts whereas CXCL9 is also largely produced by CD103 + dendritic cells within the TME [ 198 ]. Importantly, CXCL10 and CXCL9 are highly expressed by human cancer cells, and this expression is correlated with a good prognosis [ 218 , 219 , 220 , 221 , 222 , 223 , 224 , 225 ].…”
Section: Key Chemokine-chemokine Receptor Interactions That Limit Tumor Growthmentioning
confidence: 99%